2024
DOI: 10.1097/mpg.0000000000003897
|View full text |Cite
|
Sign up to set email alerts
|

An ESPGHAN Position Paper on the Diagnosis, Management, and Prevention of Cow's Milk Allergy

Abstract: A previous guideline on cow's milk allergy (CMA) developed by the European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) was published in 2012. This position paper provides an update on the diagnosis, treatment, and prevention of CMA with focus on gastrointestinal manifestations. All systematic reviews and meta-analyses regarding prevalence, pathophysiology, symptoms, and diagnosis of CMA published after the previous ESPGHAN document were considered. Medline was searched from incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 312 publications
(590 reference statements)
0
28
0
Order By: Relevance
“…We read with great interest the “letter to the editor” by Martin and Järvinen, referring to the recommendation in the guidelines on gastro‐esophageal reflux disease (GERD), published in 2018 to start an extensively hydrolyzed cow's milk based formula in case of nonacid GERD refractory to a thickened formula 1 . Martin and Jârvinen highlight that prolonged dietary elimination has been shown to have potential negative physiologic and emotional effects on the mother, on the infant, and can interrupt or end a previously successful and desired breastfeeding relationship, 2 thereby confirming the statements in the recent ESPGHAN position paper on cow's milk allergy (CMA) 3 . Marin and Järvinen stress that elimination diets should be short (2–4 weeks), with close physician follow‐up, and reintroduction/challenge should be performed 2 .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We read with great interest the “letter to the editor” by Martin and Järvinen, referring to the recommendation in the guidelines on gastro‐esophageal reflux disease (GERD), published in 2018 to start an extensively hydrolyzed cow's milk based formula in case of nonacid GERD refractory to a thickened formula 1 . Martin and Jârvinen highlight that prolonged dietary elimination has been shown to have potential negative physiologic and emotional effects on the mother, on the infant, and can interrupt or end a previously successful and desired breastfeeding relationship, 2 thereby confirming the statements in the recent ESPGHAN position paper on cow's milk allergy (CMA) 3 . Marin and Järvinen stress that elimination diets should be short (2–4 weeks), with close physician follow‐up, and reintroduction/challenge should be performed 2 .…”
mentioning
confidence: 75%
“…By stating so, the authors confirm what is written the GER guideline (“A trial of extensively hydrolyzed formula or amino acid‐based formula is indicated in patients who have not responded to conventional GERD therapies. For each of these nonpharmacologic therapies, a minimum 2‐week trial is recommended to assess for symptom improvement before considering other therapeutic alternatives”) and in the CMA position paper (“In patients not responding to conventional therapies for GERD, CMA can be considered, and, patients trialed on a time limited elimination diet for 2–4 weeks which should be followed by an oral food challenge).” 1,3 We further cite from the CMA‐position paper: “Careful consideration of the mother's commitment to breastfeed should be given full attention before advising on an exclusion diet and support provided by a nutritionist is encouraged where possible. In formula fed infants, an extensively hydrolyzed formula can be beneficial regarding regurgitation and colic probably due to enhanced gastric emptying and due to the fact that most hydrolysates are lactose free, indicating that the improvement may not be related to CMA.”…”
mentioning
confidence: 99%
“…29 Another important point is the cost-effectiveness of HRPF; in fact, in a recent study, hypoallergenic formulas accounted for the largest proportion of the total cost of managing CMPA, averaging 69% across all comparators, with a minimum of 58% for HRPF and a maximum of 87% for amino acid-based formulas. 30 However, according to the ESPGHAN position paper, 31 it is important to consider the arsenic content of HRPFs, as this is not stated for all commercial HRPFs. 32 Therefore, only HRPFs whose the arsenic content is known and within the recommended limits should be used.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the ESPGHAN position paper, 31 it is important to consider the arsenic content of HRPFs, as this is not stated for all commercial HRPFs 32 . Therefore, only HRPFs whose the arsenic content is known and within the recommended limits should be used 33 …”
Section: Discussionmentioning
confidence: 99%
“…The European Society of Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) has produced a document with recommendations relating to milk protein allergy, within which it has issued a statement also dedicated to FPIAP. 2 Addressing this gap, we, on behalf of the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP), conducted a nationwide electronic survey from January to September 2022 to provide the first analysis of allergic proctocolitis management in Italy.…”
mentioning
confidence: 99%